Role of ELT and Life Skills in Developing Employability Skills through Integrating Self Determination and Experiential Learning - Dev Brat Gupta; Vinod Bhatt; Shreya Mathur; Jyoti Badge; Asmita Sharma (Austrian Journal of Statistics)
The main purpose of this article is the combination of self-determination theory and experiential learning methodologies that explores the relationship of developing ELT, employability skill, life skills. The goal of this article is to develop a theoretical framework for life and work skills as both of these non-technical skills can be acquired by satisfying our psychological requirements for autonomy, competence, and relatedness in a classroom setting that fosters active learning. A convenient sampling technique has been used through a questionnaire-based survey of 2185 students from technical universities across India. The SPSS 29 version has been used to code and analyze the data set. Further various tests have been employed to determine Role of ELT and Life Skills in Developing Employability Skills through Integrating Self Determination and Experiential Learning. The creation of this framework is to point out how to improve one's own competence, self-assurance, intrinsic motivation, and other beneficial outcomes seen in a variety of spheres of life, including childhood, sports, and career. Consider initially how young children might acquire life skills that will promote later development of an employability skill and provide additional advantages for both the individual and the workplace. The article proposes insightful suggestions to educators and policy makers to put into practice efficient methods for incorporating experiential learning and self-determination theory into ELT and life skills curriculum.